GEOSPATIAL EFFECTS OF LANDFILL LEACHATE ON GROUNDWATER PHYSICOCHEMICAL PROPERTIES AROUND OLUSOSUN DUMPSITE, LAGOS, NIGERIA - Emmanuel, Abiodun Oludayo; Olawale, Alabi Abiodun; Luqmon, Popoola Abiodun; Folashade, Malik Aisha (Journal of Civil Engineering, Science and Technology, 2025)
Improper waste disposal is a major environmental concern. Limited resources and technology often force areas like Lagos to rely on dumpsites. However, poorly managed dumpsites can significantly harm the environment and human health. This study investigates the impact of the Olusosun dumpsite on nearby groundwater physicochemical properties. Twenty-five water samples were collected from boreholes surrounding the dumpsite and analysed in the laboratory. GPS coordinates were recorded for each sample. The Inverse Distance Weighting interpolation technique was used for interpolation of results between sampled points, creating a more complete picture of physicochemical properties of water across the study area. Test results of physicochemical properties of samples collected were compared to World Health Organisation (WHO) and Nigeria Standard for Drinking Water Quality (NSDWQ) standards. The findings showed that all the water samples had a high lead concentration. More than 50% of the water samples have zinc and copper concentrations higher than WHO and NSDWQ standards. Similarly, 52% of water samples have values outside of the normal range. Results also revealed a higher concentration of physicochemical properties in locations close to the landfill, and this reduces as the distance from Olusosun landfill increases. The study recommends an alternative source of water consumption for residents around the landfill or a proper treatment of groundwater before consumption.